2007
DOI: 10.1084/jem.20071285
|View full text |Cite
|
Sign up to set email alerts
|

Antiribosomal-P autoantibodies from psychiatric lupus target a novel neuronal surface protein causing calcium influx and apoptosis

Abstract: The interesting observation was made 20 years ago that psychotic manifestations in patients with systemic lupus erythematosus are associated with the production of antiribosomal-P protein (anti-P) autoantibodies. Since then, the pathogenic role of anti-P antibodies has attracted considerable attention, giving rise to long-term controversies as evidence has either contradicted or confirmed their clinical association with lupus psychosis. Furthermore, a plausible mechanism supporting an anti-P–mediated neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 65 publications
2
128
2
1
Order By: Relevance
“…SLE patients are known to produce more than a hundred diff erent autoantibodies (Sherer et al, 2004), but only a few of them have been directly related to pathogenic mechanisms (Matus, et al, 2007;Tsokos, 2011). We have previously shown that anti-Gal-8 autoantibodies produced by SLE patients block the interaction of Gal-8 with β1 integrins involved in its apoptotic action upon activated T cells (Norambuena et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…SLE patients are known to produce more than a hundred diff erent autoantibodies (Sherer et al, 2004), but only a few of them have been directly related to pathogenic mechanisms (Matus, et al, 2007;Tsokos, 2011). We have previously shown that anti-Gal-8 autoantibodies produced by SLE patients block the interaction of Gal-8 with β1 integrins involved in its apoptotic action upon activated T cells (Norambuena et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal study published over 20 years ago, antiribosomal P autoantibodies were detected in 90% of patients with SLE and psychosis, 45 and recent work suggests that this antibody might cross-react with a neuronal surface protein to initiate calcium influx and apoptosis. 46 However, large clinical studies and meta-analyses have reached variable results with regard to the presence of antiribosomal P antibodies in neuropsychiatric SLE, with differences attributed to laboratory methodology, study population, fluctuating course of disease, and diagnostic discrepancies. 47,48 Other groups have reported that a subset of anti-DNA antibodies in SLE cross-react with NMDA receptors, potentially resulting in neuropsychiatric abnormalities.…”
Section: Encephalopathy In Lupus and Other Systemic Syndromesmentioning
confidence: 99%
“…However, these mechanisms do not account for the majority of symptom complexes associated with NPSLE-in particular, the insidious cognitive decline manifested by up to 80% of lupus patients and the common mood disorders. Recent studies have demonstrated direct neurotoxic effects of lupus autoantibodies; antibodies to n-methyl-D-aspartate receptor (NMDAR), ribosomal P (anti-P), α-tubulin and phospholipid have been shown to bind neurons ex vivo with harmful effects (1)(2)(3)(4)(5) and all have been identified in the cerebrospinal fluid of SLE patients with CNS symptoms attributable to SLE (6)(7)(8)(9). In murine studies, circulating antibrain antibodies can cause neuronal dysfunction and apoptosis after breach of the BBB (5,(10)(11)(12), resulting in functional impairment on cognitive and behavioral tasks, as can antibodies directly injected intraventric- …”
Section: Introductionmentioning
confidence: 99%